Amalan organisasi pembelajaran di Sekolah Menengah Atas, Negeri Makassar, Indonesia - Hasbullah, Hasbullah (2017)
The Indonesian education system aims to build capacity, develop character and civilization in the nation. To realize the goal of the national education, teacher personality dimension has a very important role in the school as a learning organization, specifically referring to the school management and excellent stability in educational leadership. However, the low quality of school management in Indonesia, especially in Makassar is due to various problems such as teachers who are unqualified, lack of facilities and infrastructure, opportunities to acquire education for schooling is not stable, school management is not appropriate and graduates have difficulties to get jobs. Therefore, this study identified factors of organizational learning practices, and teachers' personalities from a government high school in Makassar, Indonesia. The research design used a mixed method. 391 respondents comprising high school teachers selected through random sampling participated in a survey. In addition, seven teachers were interviewed based on purposive sampling for the qualitative data. Quantitative data were analyzed using descriptive and inferential analysis based on the use of SPSS (Statistical Package for the Social Science). The interview data were analyzed descriptively using thematic analysis. Results showed that personality dimensions of the teachers and the development of their practice learning organizations are at a high level. There were no differences in demographic factors that determined the dimensions of the personality of teachers, and the development of their practice learning organizations. However, there was a positive and significant influence between personality dimensions of these teachers with teachers' learning organizations. Any change in the level of development of teachers' learning organization practices can be explained by the predictors of the personality dimensions of these high school teachers. The study proposed a strategy to develop the practice of learning organization in the secondary schools. Finally, this study contributes ideas and directions to assist and support teachers and principals in the practice of the learning organization, resulting in a quality education that refers to the management of schools of excellence.